ABC's of Vitamin Supplementation in Critical Illness. (December 2021) - Chudow, Melissa; Adams, Beatrice
Critical illness commonly presents as a systemic inflammatory process. Through this inflammation, there is an enhanced production of reactive oxygen and nitrogen species combined with marked reductions in protective plasma antioxidant concentrations. This imbalance is referred to as oxidative stress and is commonly encountered in numerous disease states in the critically ill including sepsis, trauma, acute respiratory distress syndrome, and burns. Oxidative stress can lead to cellular, tissue and organ damage as well as increased morbidity and mortality in critically ill patients. Supplementation with exogenous micronutrients to restore balance and antioxidant concentrations in critically ill patients has been considered for several decades. It is proposed that antioxidant vitamins, such as vitamins A and C, may minimize oxidative stress and improve clinical outcomes. Vitamin B formulations may play a role in curtailing lactic acidosis and are recently being evaluated as an acute phase reactant. However, few large, randomized trials specifically investigating the role of vitamin supplementation in the critically ill patient population are available. This article seeks to review recently published literature surrounding the role of supplementation of vitamins A, B and C in critically ill patients.